(3GdLhgQ GdfXje aj TQM YUeg GdCPgGf aj GdcTa Yf bhGYO Yde GdejRGfs - (3eMeO Hf YHO GdhgGH GdgePGfi GdeYQha HGHf OGhOs ((3eMeO SejY Hf GdMGL eMeO YdjI s)
(3ChdgG (B:s
(3GeG HYO ajbhd GdeaJbQ Edi QMeI QHg GdhOhO eMeO Hf YHO GdhgGH GdgePGfi s
(3BNQgG (B:s
(3bO HdZJ YOI CHjGJ GdefXheI Edi KeGfjI hJSYjf HjJkG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(1741) s
Keywords: (3GdadSaI hGdefWbs